Vocation and encounter: A Scandinavian theological reflection on everyday life as Christians. Issue 2 (19th June 2018) - Nahnfeldt, Cecilia
Abstract: Martin Luther turned from understanding vocation as a Christian praxis of leaving the world to understanding it as a praxis within everyday life. In accordance with such an understanding, historically, vocation in the Scandinavian countries was central for organizing society as a whole. This article discusses a contemporary use of vocation where there is a tension between communal and individual aspects in a Scandinavian context characterized by democracy, gender equality, and migration. I then propose a focus on vocation and encounter.